AUGMENTED REALITY IN EDUCATION: ENHANCING LEARNING THROUGH IMMERSIVE TECHNOLOGY - Rokade, Neel Jeeva; Wadhekar, Arti (International Journal of Research -GRANTHAALAYAH, 2025)
Augmented Reality (AR) has emerged as a transformative technology in education, offering immersive and interactive learning experiences. By integrating digital elements with real-world environments, AR enhances student engagement, comprehension, and retention. This paper explores the application of AR in educational settings, examining its benefits, challenges, and future implications. A review of existing literature, case studies, and real-world implementations assesses the effectiveness of AR in various educational contexts, demonstrating its potential to revolutionize modern learning. Furthermore, this study investigates the implementation of an IoT-based load on-off system using a NodeMCU (ESP8266) and a relay module to control an AC light bulb. The NodeMCU functions as a microcontroller, sending control signals to the relay module, which serves as an electrically operated switch. This system is widely used in IoT automation, allowing remote control of electrical appliances via Wi-Fi, enhancing convenience, efficiency, and energy management.